(3QSGdI GdEfJUGQ aj GdQO Ydi UGMH GdebGeI GdbQWHjIs - (3CHh LYaQ Hf CMeOs; (3eMeO Hf jhSa Hf YHO Gddg Hf jhSa GdJejej GdeGRfj GdSQbSWj GdCfOdSj, CHh GdWGgQ , GHf GdnCrTnJrQochfj,J (B538 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdYRI hGdLdGd GdeJhMO HGdYXeI hGdceGd GdPi JYGdi Yf UaGJ GdYGdejf hLYd GdfbU ef SeGJ GdeNdhbjf s
(3BNQgG (B:s
(3hGPcQ eG hcd EdjgeG ef GdNjQ PcQgeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B129s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1785s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs